Vein of Galen malformation with Obstructive Hydrocephalus- Endovascular Approach of Management : A Case Report - Md Shafiqul Islam; Md Motasimul Hasan; Md Sumon Rana; Md Shahnawas Biswas; Md Shahidur Rahman Sikdar; Muhammad Robiul Hoque; Hojaifa Ahmad; Md Shahid Hasan Khan; Md Atiqur Rahman (Bangladesh Journal of Neurosurgery, 2024)
The vein of Galen malformation is a rare arteriovenous shunt that is estimated to represent 30% of all pediatric vascular malformations. Less than 1% of cerebral vascular malformations are aneurysmal abnormalities of the vein of Galen, making it a rare disorder. Despite being uncommon, VGM is of particular clinical importance since the large cerebral shunt volume causes a significant mortality rate when left untreated because to date, the treatment of patients with VGM remains challenging. Here we report a case of an 11-month-old baby who had VGM with obstructive hydrocephalus and was effectively treated by transarterial glue embolization of the fistula and the venous sac. Subsequently, the baby made a complete recovery. Bang. J Neurosurgery 2023; 13(1): 34-40